A study of the soy sauce industry in Manila and the suburbs - Deniega, Marietta C. (1959)
A thorough study of the soy sauce industry in Manila and its environs is attempted in this survey. The purpose of the study is to gather necessary data for future reference in the standardization of soy sauce (toyo) manufacture and also to supply general information on this industry. Data for this study were obtained through questionnaires and interview methods. Observation was also used throughout the investigation.